Characteristics of the pelvic organ dysfunctions in patients before and after genital prolapse surgery - A.V. Smirnova; ,A.I. Malyshkina; I.A. Kolganova; N.V. Shekhlova; Z.S. Abdullaeva (LCC «Medicine-Inform», 2022)
A.V. Smirnova1,2, A.I. Malyshkina1,2, I.A. Kolganova2, N.V. Shekhlova2, Z.S. Abdullaeva2 1Ivanovo State Medical Academy, Ivanovo, Russian Federation 2V.N. Gorodkov Ivanovo Research Institute of Maternity and Childhood, Ivanovo, Russian Federation Background: descent of pelvic organs (genital prolapse, GP) of different severity is a significant medical and social problem. The key clinical manifestations in patients with GP comprise the impairment of pelvic organ functions which seriously affects the social adaptation of such patients. Aim: to assess specific clinical characteristics of the functional disorders of pelvic organs in patients with GP admitted for surgical treatment and to review changes in symptoms over time after surgery. Patients and Methods: a non-randomized prospective cohort study was carried out. The study group included 40 patients with different forms of GP, Grades II-IV under POP-Q classification system. All patients were interviewed before and 6 months after the surgical treatment using a new short version of PFDI-20 Questionnaire. Results: urinations disorders with a duration shorter than one year were reported in 19 (47%) women, from 1 year to 5 years - in 13 (32,5%), from 5 to 10 years - in 1 (2,5%), and in 4 (10%) women the symptoms lasted for more than 10 years. It was found that 12 (30%) of the interviewed women suffered from constipation, and 11 (27.5%) of patients had the feeling of incomplete defecation. Twelve (30%) patients complained of fecal and flatus incontinence. Six months after the operation, 7 (17.5%) patients mentioned some pain and discomfort in the lower abdomen. Urination disorders (urine dribble and incontinence, urethrodynia). Flatus incontinence remained in 3 (7.5) of the studied patients. Conclusion: GP reduces women's quality of life and social adaptation. Urination disorder is a principal symptom of the pelvic dysfunction. Since in 70% of women the time period from onset of first symptoms to surgical treatment exceeds 10 years, this timeframe can be used as a therapeutic window for conducting conservative therapy to correct prolapse at the outpatient stage. Keywords: descent of genitalia, genital prolapse, dysfunction of pelvic organs, dysuria, surgical treatment, vaginal delivery. For citation: Smirnova A.V., Malyshkina A.I., Kolganova I.A. et al. Characteristics of the pelvic organ dysfunctions in patients before and after genital prolapse surgery. Russian Journal of Woman and Child Health. 2022;5(3):194-200 (in Russ.). DOI: 10.32364/2618-8430-2022-5-3-194-200.